Physical and excess properties of eight binary mixtures containing water and ionic liquids - Emilio J. González (2012)
In this paper, the density, speed of sound, and refractive index of eight binary systems (water + ionic liquid) were measured, along the whole composition range, at T = (288.15 to 308.15) K and atmospheric pressure. All binary mixtures were completely miscible in water at the studied temperatures. The ionic liquids used in this work are constituted by different cations (imidazolium, pyridinium and pyrrolidinium) and anions (trifluoromethanesulfonate, dicyanamide, methylsulfate, or ethylsulfate). From the experimental data, excess molar volumes and excess molar isentropic compressions were calculated and satisfactorily fitted using the Redlich-Kister equation. Finally, the effect of the ions and temperature on the physical and excess properties was analyzed and discussed. The obtained results show that the physical and excess properties studied in this work are dependent on water content, temperature, and structure of the ILs, especially of the anion.